Synthesis and characterization of gelatin-PVP polymer composite scaffold for potential application in bone tissue engineering. (October 2019) - Mishra, Rutusmita; Varshney, Ritu; Das, Neeladrisingha; Sircar, Debabrata; Roy, Partha
Graphical abstract: Highlights: A gelatin-PVP scaffold was synthesized and characterized for functional activities. Gelatin-PVP scaffold showed remarkable biocompatibility and osteo-inductive potential. The polymer composite scaffold can be modified further for routine bone tissue engineering applications. Abstract: An ideal scaffold which mimics extracellular matrix as an artificial bone graft substitute is the need of current clinical management of orthopaedic complications. In this study, a porous biomimetic scaffold was synthesized using in situ gas foaming method. Briefly, a blend of gelatin and polyvinylpyrrolidone (PVP) was crosslinked with glutaraldehyde and lyophilized. The blending of two polymers were confirmed with FTIR, XRD and TGA analysis. The synthesized scaffold was further characterized for its biocompatibility and osteogenic potential. The physico-chemical properties like microarchitecture, porosity, water adsorption ability, and mechanical strength were also investigated. Further, the enhanced proliferation and migration of murine mesenchymal stem cells (C3H10t1/2 cells) through interconnected pores of the scaffold over an extended time period suggests the cytocompatibility of scaffold. Next, the biocompatibility of the scaffold was confirmed by in ovo implantation on the chorioallantoic membrane (CAM) using chicken embryo. In addition, increased matrix mineralization was confirmed by alizarin red staining and EDX analysis of apatite depositions over the scaffold, when induced with osteogenic media. In summary, these findings demonstrate biocompatibility and osteo-inductive potentials of the gelatin-PVP biomimetic polymer composite scaffold with suitability as bone graft substitute material.